The Relationship Between Nutritional Status and Breakfast Habits and Work Productivity Among Workers in The Processing Department of PTPN IV Regional I PKS Rambutan in Tebing Tinggi City - Tasha Nabila Ramadhani; Rani Suraya (Peneliti.net, 2026)
Work productivity is an important factor in achieving performance results and is influenced by the health and nutritional status of workers. This study aimed to examine the relationship between nutritional status and breakfast habits with work productivity among processing department workers at PTPN IV Regional I PKS Rambutan, Tebing Tinggi City. A quantitative cross-sectional design was applied with total sampling of 58 workers. Nutritional status was assessed using Body Mass Index (BMI), breakfast habits through a Food Frequency Questionnaire (FFQ), and work productivity using a structured questionnaire. Data analysis employed the chisquare test with a 95% confidence level. Results showed that 46.6% of respondents had normal nutritional status, 15.5% were overweight, and 34.5% were obese. Regarding breakfast habits, 62.1% were in the sufficient category and 24.1% in the poor category. Statistical analysis revealed a significant relationship between nutritional status and work productivity (p = 0.000) as well as between breakfast habits and work productivity (p = 0.008). Workers with normal nutritional status and good breakfast habits tended to have higher productivity, while obesity and poor breakfast habits were associated with lower performance. It is concluded that maintaining a balanced nutritional status and regular breakfast consumption can improve productivity. Companies should implement workplace nutrition programs, encourage healthy eating patterns, and facilitate access to nutritious breakfasts before working hours.